Impacts of market-based contractual arrangements with farmers in Guatemala and Honduras - Delgado, Luciana; Nakasone, Eduardo; Torero, Máximo (International Food Policy Research Institute, 2021)
Globally, initiatives have addressed food insecurity and the increasing pressure on available land that has followed from growing populations and changing diets. These policies, however, have been aimed mainly at increasing agricultural yields and productivity and are often cost- and time-intensive. They have not focused on reducing food losses, nor considered food loss reduction as a tool that can help meet growing food demand. Any interventions in food value chains will have three impacts: (1) improvements in food security and nutrition through increasing food availability (which addresses Sustainable Development Goal [SDG] 2: Zero hunger); (2) improvements in productivity and economic growth, as farmers will be able sell more produce in the markets (SDG 8: Decent work and economic growth); and (3) emissions reductions (SDG 13: Climate action) and improved efficiency in natural resource use, especially use of water and land (SDG 14: Life below water; SDG 15: Life on land).